“Safeguarding the Right to Data Protection in the EU”, 30th and 31st October 2014, Paris, France - Mistale Taylor (Utrecht Journal of International and European Law, 2015)
This contribution is based on presentations and discussions at the conference “Safeguarding the Right to Data Protection”, held in Paris on the 30th and 31st October, 2014. Vladimir Marinescu, of the Academy of European Law (hereafter: ERA), in cooperation with the Cour de Cassation, organised the event. The conference looked at developments in EU data protection law with a focus on data protection as a fundamental right. Speakers discussed recent jurisprudence from the Court of Justice of the European Union (hereafter: CJEU or the Court), the European Court of Human Rights (hereafter: ECtHR) and national courts. The conference covered four main focus areas: EU data protection law; civil and criminal law aspects of data protection and the internet; data protection as a cornerstone of European fundamental rights protection; and data protection remedies. This contribution elaborates upon some of the most pertinent issues speakers discussed.